SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM UPAYA MENANAMKAN NILAI SIKAP NASIONALISME MELALUI PEMBELAJARAN PPKN DI SMA DARMA YUDHA - Dinda Lianisari; Almasdi Syahza; Sumardi Sumardi (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2022)
The influence of the globalization era can decrease the sense of nationalism, and it can be seen from the students in Indonesia. School is one of the institutions that can be used to develop the sense of nationalism in the younger generation, for example through the civic education and also other school activities. In terms of improving teachers’ performances in school, one of the important factors that can not be ignored is the ideal supervision from the school principal. This is the reason why the research about Darma Yudha Senior High School principal’s supervision in an attempt to develop a sense of nationalism through civic education was conducted. This research is a qualitative descriptive study. The data was collected by doing observations, interviews, and documentation. This research was conducted at Darma Yudha Senior High School, Pekanbaru, Riau Province. In general, this study aims to find out the school principals’ academic supervision as an attempt to develop a sense of nationalism through civic education. There were 8 respondents in this research, which are 1 school principal, 5 vice principals, and 2 civic education teachers. The results of the research are: (1) There are three indicators used by the principal in supervising the civic education teachers, (2) The procedure in doing academic supervision consists of three stages, from planning to reporting, (3) The achievement of teachers’ performances in developing the sense of nationalism is used by the school principal, teachers, and human resource department in planning, implementing and evaluating the school as an institution that implements the education of cultural and national characters, (4) To develop the sense of nationalism in the school, Darma Yudha Senior High School creates routine program activities as well as the activities that are conducted only during certain events, and (5) Evaluations carried out by teachers and principals in developing a sense of nationalism are carried out in a derivative concept. First, the principal conducts direction and guidance to the teachers, and then the teachers give them to the students as well.